Tax revenues in the European Union : recent trends and challenges - Carone, Giuseppe; Nicodeme, Gaetan; Schmidt, Jan H.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
The governments of the European Union are facing important challenges that may impact both their need and their capacity to collect taxes. First, ageing will increase some social spending while reducing the potential of some tax bases such as labour. Second, globalisation has the potential to increase the mobility of capital and of high-skilled workers, making it more difficult to rely on them as a source of revenues. Finally, the desire to shift tax away from labour and to make work pay while retaining the social models will force Member States to find alternative robust tax bases. This paper reviews the most recent trends in taxation in the European Union and discusses several tax policy issues in the light of those coming challenges.
Economic Papers